1989
DOI: 10.1016/0735-1933(89)90004-3
|View full text |Cite
|
Sign up to set email alerts
|

Apparatus for investigating boiling phenomena in a fibrous porous medium

Abstract: Recent advances in paper drying research have identified a phase-change process that offers significant improvements in drying rates and sheet solids contents. A fundamental study focusing on the hypothesized boiling process within the sheet required the development of an apparatus to perform boiling experiments in a bed of ceramic fibers. The apparatus is composed of a boiling cell, a heat supply system, a digital data acquisition system, and associated process control systems for control of heater surface te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…This issue is due to the changing of properties of heat transfer surface, because of the sedimentation of nanoparticles and creation of the thin film layer on the heater surface. Rudemiller (1989), in a research about boiling phenomenon, studied the phase changing in a porous medium. In the mentioned study, the porous surface has been considered to be made of ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…This issue is due to the changing of properties of heat transfer surface, because of the sedimentation of nanoparticles and creation of the thin film layer on the heater surface. Rudemiller (1989), in a research about boiling phenomenon, studied the phase changing in a porous medium. In the mentioned study, the porous surface has been considered to be made of ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the increase in heat transfer per pressure drop unit occurs in a porosity ratio of 0.7. Rudemiller et al [12] studied a phase change in a porous medium. The results showed that the porous medium has a great influence on heat transfer enhancement.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve a better understanding of the role of boiling heat transfer in impulse drying, this research addresses the effects of a fibrous medium possessing significant capillary forces on the characteristic boiling curve over a broad range of surface temperature. The experimental apparatus designed to gather data for boiling of water in a fibrous medium, illustrated in Figure 2, is discussed in detail elsewhere (Rudemiller, 1989;Rudemiller and Lindsay, 1989). Briefly, the boiling cell apparatus is composed of four systems: the boiling cell, the heat supply system, the data acquisition system, and the process control system.…”
Section: Introductionmentioning
confidence: 99%